Surgical time and complications of total transvaginal (total-NOTES), single-port laparoscopic-assisted and conventional ovariohysterectomy in bitches - Silva, M. A. M.; Toniollo, G. H. [UNESP]; Flores, F. N.; Valadão, C. A. A. [UNESP]; Medeiros, R. M. [UNESP]; Cardilli, D. J. [UNESP]; Gering, A. P. [UNESP]; Teixeira, P. P. M; Serafini, G. M. C.; Coutinho-Júnior, A. S.; Libardoni, R. N.; Brun, M. V. (Universidade Federal de Minas Gerais, Escola de Veterinária, 2015)
The recently developed minimally invasive techniques of ovariohysterectomy (OVH) have been studied in dogs in order to optimize their benefits and decrease risks to the patients. The purpose of this study was to compare surgical time, complications and technical difficulties of transvaginal total-NOTES, single-port laparoscopic-assisted and conventional OVH in bitches. Twelve bitches were submitted to total-NOTES (NOTES group), while 13 underwent single-port laparoscopic-assisted (SPLA group) and 15 were submitted to conventional OVH (OPEN group). Intra-operative period was divided into 7 stages: (1) access to abdominal cavity; (2) pneumoperitoneum; approach to the right (3) and left (4) ovarian pedicle and uterine body (5); (6) abdominal or vaginal synthesis, performed in 6 out of 12 patients of NOTES; (7) inoperative time. Overall and stages operative times, intra and postoperative complications and technical difficulties were compared among groups. Mean overall surgical time in NOTES (25.7±6.8 minutes) and SPLA (23.1±4.0 minutes) groups were shorter than in the OPEN group (34.0±6.4 minutes) (P<0.05). The intraoperative stage that required the longest time was the approach to the uterine body in the NOTES group and abdominal and cutaneous sutures in the OPEN group. There was no difference regarding the rates of complications. Major complications included postoperative bleeding requiring reoperation in a bitch in the OPEN group, while minor complications included mild vaginal discharge in four patients in the NOTES group and seroma in three bitches in the SPLA group. In conclusion, total-NOTES and SPLA OVH were less time-consuming then conventional OVH in bitches. All techniques presented complications, which were properly managed.

O emprego de novas técnicas minimamente invasivas de ovário-histerectomia (OHE) vem sendo estudado em cães com o intuito de otimizar seus benefícios e reduzir os riscos aos pacientes. O presente estudo objetivou comparar o tempo cirúrgico, as complicações e dificuldades técnicas entre as abordagens por total-NOTES transvaginal, videoassistida com único portal e por celiotomia para ovário-histerectomia (OVH) em cadelas. Foram operados 12 animais por total-NOTES (grupo NOTES), 13 pela técnica videoassistida (grupo SPLA) e 15 pela técnica convencional (grupo OPEN). O período intraoperatório foi dividido em sete etapas: (1) acesso à cavidade abdominal; (2) criação do pneumoperitônio; abordagem ao pedículo ovariano direito (3), esquerdo (4) e ao corpo uterino (5); (6) síntese abdominal ou vaginal, realizado em seis de 12 pacientes do grupo NOTES; (7) tempo inoperante. Os parâmetros avaliados foram o tempo cirúrgico total e de cada etapa intraoperatória, a frequência de complicações intra e pós-operatórias e dificuldades técnicas. O tempo cirúrgico total médio dos grupos NOTES (25,7±6,8 minutos) e SPVA (23,1±4,0 minutos) foram menores que o do grupo OPEN (34,0±6,4 minutos) (P<0.05). A etapa intraoperatória que demandou maior tempo de execução foi a abordagem ao corpo uterino para o grupo NOTES, e síntese abdominal e cutânea para o grupo OPEN. Uma cadela do grupo OPEN necessitou de reintervenção para controle de hemorragia como complicação maior, e três cadelas do grupo SPVA apresentaram seroma de ferida cirúrgica como complicações menores. Concluiu-se que as técnicas de total-NOTES e SPLA apresentaram menor tempo cirúrgico que a abordagem convencional de OVH em cadelas. Todas as técnicas apresentaram complicações que foram adequadamente manejadas.
Tempo cirúrgico e das complicações entre as técnicas de ovário-histerectomia totalmente transvaginal (total-NOTES), videoassistida com único portal e convencional em cadelas
Keywords: Canine; spay; lAparoscopy; Operative time; Transvaginal approach; Caninos; Castração; lAparoscopia; Tempo operatório|Labordagem transvaginal